2019
DOI: 10.1186/s13104-019-4483-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and etiological agents for chronic suppurative otitis media in a tertiary hospital in Tanzania

Abstract: Objective Chronic suppurative otitis media is among the most common otological condition reported in otorhinolaryngology practice commonly attributing to preventable hearing loss. The aim of this study was to determine the prevalence and etiological agents for chronic suppurative otitis media in our department. Results A total of 5591 patients were recruited in this study and only 79 (1.4%) had chronic suppurative otitis media. A male preponderance 43 (54.4%) was noted … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 23 publications
5
23
0
7
Order By: Relevance
“…The study found that many ear infections are of bacterial aetiology. The finding is similar to studies done in Tanzania by Kennedy et al in Morogoro, 4 Zephania et al in Dar es Salaam, 15 Martha et al in Mwanza 3 and other studies in Kenya and India. 16 17 Furthermore, we observed that S. aureus and P.s aeruginosa are ear infections’ leading bacterial aetiological agents, similar to previous studies in Tanzania, Nigeria, Angola, Kenya and India.…”
Section: Discussionsupporting
confidence: 91%
“…The study found that many ear infections are of bacterial aetiology. The finding is similar to studies done in Tanzania by Kennedy et al in Morogoro, 4 Zephania et al in Dar es Salaam, 15 Martha et al in Mwanza 3 and other studies in Kenya and India. 16 17 Furthermore, we observed that S. aureus and P.s aeruginosa are ear infections’ leading bacterial aetiological agents, similar to previous studies in Tanzania, Nigeria, Angola, Kenya and India.…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, the culture yield compared to the side of the ear showed a statistically significant p-value (0.015) (Table 4). 12,13 In the current study, the presence of pus in the right ear (51%) and pus in the left was reported in (49%) of the patients. However, previous studies by Abraham et al infer that the right ear was affected more.…”
Section: Resultssupporting
confidence: 45%
“…Rohan et al have similar findings where Pseudomonas species were the most common 14. In the study by Gupta et al and Abraham et al, Klebsiella species was the most common 12,15.…”
mentioning
confidence: 69%
“…The present study indicated that patients aged 10-19 years had the highest incidence of ear infections, which is consistent with previous studies which reported that most ear infections occurred in people less than 20 years old. [13][14][15][16] The short, broad, and straight structure of the eustachian tube, in addition to poor hygiene, a weakened immune system, frequent exposure to upper respiratory tract infections, and malnutrition may all contribute to the higher prevalence of ear infections in children compared to that observed in adults. 3,8,17 Furthermore, ear infections were slightly more common in men than women (58% vs 42%, respectively), but no significant difference was observed, which agrees with the findings of previous studies.…”
Section: Discussionmentioning
confidence: 99%